Devaluation-bias and the Bretton Woods System. A comment - HEIN, J. (PSL Quarterly Review, 2013)
In this brief note, the author comments on Samual I. Katz’ “Devaluation-Bias and the Bretton Woods System”, arguing that the alleged devaluation-bias of the Bretton Woods system may have reflected prevailing conditions and circumstances rather than any inherent defect in international monetary arrangements. JEL: E42, F33